2021
DOI: 10.1186/s12903-021-01540-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of scaler tip design on root surface roughness, tooth substance loss and patients’ pain perception: an in vitro and a randomised clinical trial

Abstract: Background The influence of scaler tip design on root surface roughness, tooth substance loss and patients’ pain perception is investigated. Methods This article was divided into the following parts: Part 1 Surface roughness and substance loss: an in vitro study, which involves intact extracted teeth sectioned and treated using a piezoelectric ultrasonic device (PM200 EMS Piezon, Switzerland) with a conventional scaler tip (FS-407) and a Perio Sli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…However, Busslinger et al 9 demonstrated that the scaling efficiency of piezoelectric ultrasonic scalers is significantly greater than that of magnetostrictive ultrasonic scalers. This difference in results may be attributed to variations in the brands, working tips, and lateral forces of the periodontal instruments used in our experiments 29 31 .…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…However, Busslinger et al 9 demonstrated that the scaling efficiency of piezoelectric ultrasonic scalers is significantly greater than that of magnetostrictive ultrasonic scalers. This difference in results may be attributed to variations in the brands, working tips, and lateral forces of the periodontal instruments used in our experiments 29 31 .…”
Section: Discussionmentioning
confidence: 85%
“…The generator produces an electric or magnetostrictive field, and the transducer converts high-frequency electric or electromagnetic energy into ultrasonic vibrations. However, the mechanical friction of the scaler tips can cause scratches or minor damage to the tooth surface 29 . Furthermore, ultrasonic scaling produces noise and vibration, which may cause temporary discomfort or pain to patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the use of Mini-Five Gracey curettes resulted in greater PD reduction and lower gingival recession. Regarding power-driven devices, a recent randomized clinical trial compared three different sizes of piezoelectric ultrasonic scaler tips for in vitro and clinical analyses [ 47 ]. The results showed that using a slim-designed scaler tip caused less tooth substance loss and less pain experience for patients than a conventional wide scaler tip.…”
Section: Discussionmentioning
confidence: 99%